Pengaruh Upah Minimum, Produk Domestik Regional Bruto, Pendidikan dan Tingkat Partisipasi Angkatan Kerja Terhadap Tingkat Pengangguran Terbuka di Provinsi Sumatera Barat - Hardika Vanzani; Urmatul Uska Akbar (Universitas Negeri Padang, 2025)
Abstract: This research aims to analyze how the Minimum Wage, Gross Regional Domestic Product (GRDP), Education, and Labor Force Participation Rate influence the Open Unemployment Rate in West Sumatra Province. The study employs panel data analysis using the Fixed Effect Model (FEM). The Open Unemployment Rate serves as the dependent variable, with Minimum Wage, GRDP, Education, and Labor Force Participation Rate as the independent variables. Findings reveal that both minimum wage and education exert a positive yet statistically insignificant impact on the open unemployment rate, while Gross Regional Domestic Product and labor force participation rate significantly and negatively affect the unemployment level.